2010
DOI: 10.1128/jcm.01636-09
|View full text |Cite
|
Sign up to set email alerts
|

PCR Using Blood for Diagnosis of Invasive Pneumococcal Disease: Systematic Review and Meta-Analysis

Abstract: The use of molecular-based methods for the diagnosis of bacterial infections in blood is appealing, but they have not yet passed the threshold for clinical practice. A systematic review of prospective and case-control studies assessing the diagnostic utility of PCR directly with blood samples for the diagnosis of invasive pneumococcal disease (IPD) was performed. A broad search was conducted to identify published and unpublished studies. Two reviewers independently extracted the data. Summary estimates for sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 64 publications
2
44
0
Order By: Relevance
“…Moreover, in the metaanalysis by Avni et al [17] the rate of diagnosis by positive PCR was also higher than the rate by positive blood culture in 16 of 25 studies.…”
Section: P=04)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the metaanalysis by Avni et al [17] the rate of diagnosis by positive PCR was also higher than the rate by positive blood culture in 16 of 25 studies.…”
Section: P=04)mentioning
confidence: 99%
“…al. [17] have published an accurate meta-analysis and found that the studies were highly heterogeneously including different type of PCR methods [18,19], different target genes [20], most used stored frozen [21] and different samples (i.e. whole blood or plasma) [22], as well as different patients' characteristics and different clinical syndromes [23,24].…”
Section: Reproducibility and Specificity Of Real-time Pcrmentioning
confidence: 99%
“…In pneumococcal pneumonia, blood cultures often remain negative and polymerase chain reaction (PCR)-based detection of Streptococcus pneumoniae in patients with a clinical suspicion for pneumonia has been shown to be more sensitive than blood cultures in clinical studies [6,7]. However, in a recent meta-analysis of 29 studies, published between 1993 and 2009, the authors concluded that PCR from blood samples for the diagnosis of invasive S. pneumoniae infection lacks the sensitivity and specifi city necessary for clinical practice [8]. This meta-analysis highlights the problems associated with determining accuracy of a diagnostic test.…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…Real-time PCR is theoretically useful for the diagnosis of IPD. However, these techniques are not in routine use for diagnosing pneumococcal infections and must be evaluated to ascertain their value among the tools used for clinical diagnoses especially when PCR is performed from blood samples [7]. PCR-based methods usually target the ply gene encoding pneumolysin and the lytA gene encoding autolysin.…”
Section: Introductionmentioning
confidence: 99%